Gasdermin-D pores induce an inactivating caspase-4 cleavage that limits IL-18 production in the intestinal epithelium - J. K. Bruce; L. Y. Li; Y. Tang; E. Forster; N. J. Winsor; P. Y. Bi; C. Krustev; S. Keely; J. E. Lee; J. R. Rohde; H. Y. Gaisano; D. J. Philpott; et al. (Communications Biology)
Abstract Intestinal epithelial-derived IL-18 is critical for homeostatic intestinal barrier function and is secreted through Gasdermin D (GSDMD) pores. Inflammasome activation is a prerequisite for both IL-18 maturation and GSDMD pore formation. However, GSDMD pores also cause pyroptotic cell death, which could be detrimental to the intestinal epithelial barrier. How epithelial cells balance the need to secrete IL-18 and to maintain barrier integrity remains poorly understood. In human intestinal epithelial cell lines and in primary human epithelial intestinal organoids, but not in immune cells, GSDMD plasma membrane pore formation by LPS electroporation and by gram-negative bacterial infection induced a non-conventional p37 caspase-4 fragment that was associated with reduced levels of mature IL-18. By contrast, limiting GSDMD plasma membrane pores pharmacologically and via point-mutagenesis prevented caspase-4 cleavage and increased IL-18 production, suggesting that p37 caspase-4 cleavage may regulate IL-18 maturation in the intestinal epithelium. In support, co-expression of caspase-4 cleavage mutants and IL-18 in HEK293T cells revealed that non-cleavable caspase-4 produced more mature IL-18 than cleaved caspase-4. Overall, these studies suggest that epithelial inflammasomes encode feedback pathways that control the balance between cytokine secretion and cell death. This may be an important mechanism to ensure homeostatic IL-18 production in the intestinal epithelium.